2020
DOI: 10.1016/j.vas.2020.100145
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of observer ratings: Qualitative behaviour assessments of shelter dogs using a fixed list of descriptors

Abstract: Qualitative Behaviour Assessment (QBA) is a whole-animal approach used to quantify the expressive style of animals’ behaviour. The aim of this study was to evaluate the inter-observer reliability of QBA of shelter dogs using a fixed list of descriptors. The fixed list of 20 terms was generated using a group of experts and literature reviews. In the pilot study, seven veterinary students scored 12 two-minute video clips, and in the main study, 22 final year veterinary nurse students and third-year veterinary st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…The anchoring points for the principal components were similar to the anchoring points in Part I (Fig. 2), and comparable to the previous study [9]. The first component (PC1) in both parts of the study reflects the dogs' mood, while the second component (PC2) appears to be related to arousal.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The anchoring points for the principal components were similar to the anchoring points in Part I (Fig. 2), and comparable to the previous study [9]. The first component (PC1) in both parts of the study reflects the dogs' mood, while the second component (PC2) appears to be related to arousal.…”
Section: Resultssupporting
confidence: 86%
“…In a previous study, Stubsjøen et al [9] found a high inter-observer reliability when observers used a fixed list of descriptors to assess videos of shelter dogs. To evaluate the robustness of this finding, we replicated the study by using the same fixed list of descriptors and video recordings to reassess inter-observer reliability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After listening to each meow (participants could replay each sound ad libitum), participants were asked to choose one out of three possible contexts in which the vocalization was emitted (i.e., waiting for food, isolation, brushing), to indicate the emotional state of the meowing cat in terms of valence (positive vs. negative), and to give a score on a 7-point Likert scale to 11 descriptors of the possible emotional state: agitated/anxious, aggressive/angry, frustrated, restless/nervous, frightened, suffering, friendly, calm/relaxed, happy, curious, and playful. This procedure was based on previous research using qualitative behavior assessment in companion animals (dogs) [ 80 ] and reminds sociolinguistic researchers to investigate attitudes toward different aspects of language [ 81 , 82 ]. Between the proposed sounds, a 5-second pink noise sample was reproduced in order to avoid direct comparison.…”
Section: Materials and Methodsmentioning
confidence: 99%